Thermal, chemical, and structural investigation of the usability of Cs/nHAp-ZnO/Glutaraldehyde polymer matrix composite in potential biomaterial applications - Yigit, Oktay (Elsevier, 2023)
Nano-HAp and ZnO-containing particles in the main chitosan matrix that can be used as a scaffold composite or surface coating in dental and medical implants to improve infection and biocompatibility processes have been developed. After adding chitosan/HAp-ZnO biopolymer, a cross-linked triple absorbent composite system was produced using glutaraldehyde simply and practically. Morphological analyzes were examined by FE-SEM analysis, and the changes that occurred with the cross-linking reaction were observed. Elemental analysis of composite materials was analyzed with EDS, and chemical analyzes were analyzed using ART-IR, XPS XRD and Raman analyses. In addition, the thermal properties of the composites were examined by DTA and TGA analysis. As a result of the cross-linking reaction, it was observed that the composite exhibited a more compact structure. The study's primary purpose was to observe the ability of the biodegradable chitosan polymer to form composites with ZnO and HAp structure and examine the changes that occur with the cross-linking reaction. As a result, it was seen that the three components were well distributed among each other, intramolecular and intermolecular bonds were formed between these components, and the composite was restructured with the occurrence of strong interaction. (c) 2023 The Author(s). Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Chitosan; Hydroxyapatite; ZnO; Polymeric Composites; Cross-linking reaction